2022
DOI: 10.1111/bjh.18183
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy after PD‐1 inhibitors in relapsed/refractory Hodgkin lymphoma: Outcomes and clonal evolution dynamics

Abstract: Summary Checkpoint inhibitors (CPIs) are routinely employed in relapsed/refractory classical Hodgkin lymphoma. Nonetheless, persistent long‐term responses are uncommon, and one‐third of patients are refractory. Several reports have suggested that treatment with CPIs may re‐sensitize patients to chemotherapy, however there is no consensus on the optimal chemotherapy regimen and subsequent consolidation strategy. In this retrospective study we analysed the response to rechallenge with chemotherapy after CPI fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…While our patient population had a significant load of risk factors and prior treatments, together with a substantial rate of uncontrolled (PET-positive) disease at transplantation, the high rate of pre-ASCT exposure to anti-PD1 might have biologically counterbalanced these adverse factors by promoting a better efficacy of HDT conditioning. Several studies, in patients with chemorefractory RR-HL, have documented that treatment with anti-PD1, likely due to a clonal ‘reshaping’ effect, enhance/restores sensitivity to anticancer agents, including those present in the conditioning regimens for ASCT [ 32 , 33 , 34 ]. In addition, an important real-life study indicated that using PD-1 blockade as a bridge to ASCT in chemorefractory patients was associated with excellent post-transplantation outcomes, without any apparent improvement by post-ASCT treatment with anti-PD1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While our patient population had a significant load of risk factors and prior treatments, together with a substantial rate of uncontrolled (PET-positive) disease at transplantation, the high rate of pre-ASCT exposure to anti-PD1 might have biologically counterbalanced these adverse factors by promoting a better efficacy of HDT conditioning. Several studies, in patients with chemorefractory RR-HL, have documented that treatment with anti-PD1, likely due to a clonal ‘reshaping’ effect, enhance/restores sensitivity to anticancer agents, including those present in the conditioning regimens for ASCT [ 32 , 33 , 34 ]. In addition, an important real-life study indicated that using PD-1 blockade as a bridge to ASCT in chemorefractory patients was associated with excellent post-transplantation outcomes, without any apparent improvement by post-ASCT treatment with anti-PD1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher risk of NRM hampers the success of Allo-SCT compared with BV and CPI therapy or with ASCT. Recent studies have suggested that CPI may have a chemosensitizing effect [33,34], with an ORR of 66-82% achieved with a rechallenge with IGEV or BEGEV chemotherapy, allowing for R/R HL patients to be bridged to Allo-SCT. Given the renovated chemosensitivity, HDT/ASCT was rechallenged as a consolidation strategy in R/R HL rescued with CPI, showing a promising 18-month PFS and OS of 81% and 96%, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…These results make us glimpse at the ability of CPIs to not only direct the host’s immune response against the tumour, but also to restore its sensitivity to classical chemotherapeutical compounds with molecular mechanisms that are still widely unknown. Of note, one among these retrospective studies depicts a particularly high response rate in patients undergoing chemotherapy with the Gemcitabine-based regimen, and the authors speculate that these high response rates might be attributed to the ability of Gemcitabine to influence the tumour-directed immune response ( 79 ).…”
Section: Checkpoint Inhibitors In Clinical Trialsmentioning
confidence: 99%